Productivity and NPK uptake by maize as influenced by conjunctive use of FYM, lime and fertilizers in an acid Alfisol - BHARTI, ANUPAM; SHARMA, R. P.; SANKHYAN, N. K.; KUMAR, RAMESHWAR (Journal of Soil and Water Conservation, 2021)
A field experiment was conducted on maize crop during kharif 2019 at experimental farm of the department of Soil Science, CSKHPKV, Palampur to study the effect of conjoint use of FYM and lime along with recommended dose of fertilizers on yield and NPK uptake by maize in acid soils of Palampur (Himachal Pradesh). The experiment was laid out in a randomized block design with eleven treatments replicated thrice. Results revealed that integrated use of FYM and lime along with recommended dose of fertilizers recorded significantly higher grain and stover yield as compared to separate use of FYM or lime with recommended dose of fertilizers. Application of 100% NPK + 10 t FYM/ha + lime incorporation @ 100% Lime Requirement (LR) showed a yield response of 22.4 q/ha, 12.9 q/ha and 13.9 q/ha over 100% NPK alone (T2), 100% NPK + 10 t FYM/ha and 100% NPK + lime incorporation @ 100% LR, respectively. The grain yield of maize (34.90 q/ha) recorded under 100% NPK + 10 t FYM/ha + lime incorporation @ 1/10th LR in furrow was at par with 100% NPK + 10t/ha FYM/ha + lime incorporation @ 100% LR (36.48 q/ha). Integrated use of FYM, lime and 100% NPK increased the NPK uptake significantly over 100% NPK. The highest N, P and K uptake was recorded in 100% NPK + 10 t FYM/ha + lime incorporation @ 100% LR. Hence, it can be inferred from the study that conjunctive use of FYM and lime along with optimal doses of fertilizers is essential to enhance the productivity of maize in acid soils. The dose of lime can be reduced by applying lime in furrow instead of broadcasting.